2021
DOI: 10.3389/fpls.2021.665014
|View full text |Cite
|
Sign up to set email alerts
|

An Antisense Circular RNA Regulates Expression of RuBisCO Small Subunit Genes in Arabidopsis

Abstract: Circular RNA (circRNA) is a novel class of endogenous long non-coding RNA (lncRNA) and participates in diverse physiological process in plants. From the dataset obtained by high-throughput RNA sequencing, we identified a circRNA encoded by the sense strand of the exon regions spanning two RuBisCO small subunit genes, RBCS2B and RBCS3B, in Arabidopsis thaliana. We further applied the single specific primer-polymerase chain reaction (PCR) and Sanger sequencing techniques to verify this circRNA and named it ag-ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…PIN2pro:PIN2-GFP (eir 1-1 background) and DR5pro:GFP were obtained from Rujin Chen (Noble Foundation, Ardmore, OK, USA) [20,21] and grown for 5 days in solid medium with 1, 10, 100, 300 μg/mL LDH or 1, 10, 100 μg/mL RM, as described in Step "Plant material and growth conditions". Then, these seedlings were observed under a laser scanning confocal microscopy system (Leica SP8, USA), and analyzed using ImageJ software (National Institutes of Health, USA), with parameters as previously described [16]. The green fluorescent protein (GFP) and FITC fluorescence was excited with a 488 nm laser, and the emission fluorescence was collected at wavelengths between 500 and 550 nm.…”
Section: Confocal Laser Scanning Microscopy Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…PIN2pro:PIN2-GFP (eir 1-1 background) and DR5pro:GFP were obtained from Rujin Chen (Noble Foundation, Ardmore, OK, USA) [20,21] and grown for 5 days in solid medium with 1, 10, 100, 300 μg/mL LDH or 1, 10, 100 μg/mL RM, as described in Step "Plant material and growth conditions". Then, these seedlings were observed under a laser scanning confocal microscopy system (Leica SP8, USA), and analyzed using ImageJ software (National Institutes of Health, USA), with parameters as previously described [16]. The green fluorescent protein (GFP) and FITC fluorescence was excited with a 488 nm laser, and the emission fluorescence was collected at wavelengths between 500 and 550 nm.…”
Section: Confocal Laser Scanning Microscopy Observationsmentioning
confidence: 99%
“…Song [15] used LDH-lactate-NS to transport lncRNAs into live seedling lateral roots of Populus simonii to mimic overexpression and interference. Furthermore, Zhang [16] used LDH-lactate-NS to deliver in vitro synthesized circRNA named ag-circRBCS into Arabidopsis thaliana seedlings, and indicated that ag-circRBCS significantly depressed the expression of the RBCS gene. LDHs can also be used for plant disease resistance, maintaining the long-term plant resistance of RNA insecticides and reducing the cost of biological agents [17,18]: (i) LDHs protects RNA and enables it to remain on plant leaves for a long time to avoid losing its medicinal activity or being washed away by rain; (ii) LDHs slowly degrades and releases RNA to prolong its pest resistance; (iii) LDH nanosheets decompose and form biofriendly inorganic ions (e.g., magnesium ions) for plant growth, to completely avoid soil secondary pollution.…”
Section: Introductionmentioning
confidence: 99%
“…For example, overexpression of Os08circ16564 in rice reduces the expression level of its parental gene ( AK064900 ) in transgenic plants ( Lu et al., 2015 ). Delivery of ag-circRBCS synthesized in vitro into Arabidopsis seedlings using the delaminated layered double hydroxide lactate nanosheet method significantly depresses the expression of RBCS ( Zhang et al., 2021a ). Overexpression of PSY1-circ1 derived from the PSY1 inhibits the accumulation of mRNA from its parental gene PSY1 in tomato ( Tan et al., 2017 ).…”
Section: Mechanisms Of Action Of Circrnas In Plantsmentioning
confidence: 99%
“…Based on the chromosomal location from which they are derived, circRNAs can be classified into exonic circRNAs (EcircRNAs), circular intronic RNAs (ciRNAs), exon–intron circRNAs (ElciRNAs), intergenic circRNAs, intergene-exon circRNAs, and intergene-intron circRNAs ( Zhang et al., 2020b ). Most circRNAs are usually derived from a single protein-coding gene, and individual circRNAs can be derived from more than one protein-coding gene, such as ag-circRBCS from the exonic regions of the two genes RBCS2B and RBCS3B ( Zhang et al., 2021a ). Alternative back-splicing events are widespread in plant circRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials have successfully been used to deliver almost all kinds of biomolecules into the plants, to change the expression of target genes constitutively or transiently (Wang et al, 2019). For instance, single-walled carbon nanotube (SWNT) and mesoporous silica nanoparticles (MSNs) enabled penetration of plasmid DNA into intact plant cells (Chang et a., 2013;Demirer et al, 2019), magnetic nanoparticles acted as carriers to transfer exogenous genes into cotton and maize seeds via their pollen tubes (Zhao et al, 2017;Wang et al, 2021), LDH-NSs were used to transfer dsRNA (Mitter et al, 2017;Yong et al, 2021Yong et al, , 2022, long noncoding RNA (lncRNA) (Song et al, 2019), small interfering RNA (siRNA) (Zhang et al, 2022a), and circular RNA (circRNA) (Zhang et al, 2021) in different types of intact cells of different plant species to regulate the expression levels of target genes.…”
Section: Introductionmentioning
confidence: 99%